Antipodal Polygons and Their Group Properties - Medianik, A.I. (Журнал математической физики, анализа, геометрии, 2012)
We study the groups of transformations which transform antipodal polygons into antipodal ones as well as their order and the number of equivalence classes of n-gons inscribed into the regular (2n - 1)-gon.